(untitled) (Open Academia: Journal of Scholarly Research, 2026)
This article analyzes the history of the earliest archaeological investigations conducted in the cities of the Kashkadarya oasis in Southern Uzbekistan, with particular emphasis on the cities of Karshi and Kesh–Shahrisabz. It highlights the scholarly significance of historicaltopographical, architectural, and archaeological studies carried out from the early twentieth century until the late 1940s by researchers such as I. Castagné, L. Zimin, V. V. Bartold, A. Yu. Yakubovsky, M. E. Masson, and others. The results of the study demonstrate that the initial archaeological research laid an important scientific foundation for investigating the historical development, urban planning traditions, and tangible cultural heritage of the cities of the Kashkadarya oasis.